2016
DOI: 10.1080/02688697.2016.1199787
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid rhinorrhea: evaluation with 3D-SPACE sequence and management with navigation-assisted endonasal endoscopic surgery

Abstract: MR imaging with 3D-SPACE sequence is an effective and reliable method with higher sensitivity and specificity than T2W for detecting CSF leakage. Intraoperative 3D-SPACE image-guided navigation is helpful in locating the sites of the CSF leakage during endonasal endoscopic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…This makes it difficult to rule in a diagnosis and identify an active site in the context of multiple leaks. 35,41,48…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This makes it difficult to rule in a diagnosis and identify an active site in the context of multiple leaks. 35,41,48…”
Section: Discussionmentioning
confidence: 99%
“…This makes it difficult to rule in a diagnosis and identify an active site in the context of multiple leaks. 35,41,48 MR imaging directly visualizes fistulous tracts without ionizing radiation or interference from bony artifacts. 35 However, the presence of inflammation may cause false positives given its similarly hyperintense signal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One‐hundred and fourteen abstracts described HRCT and CSF rhinorrhea; 16 studies reported sensitivities ranging from 43% to 100% . One hundred and twenty‐four abstracts described MRC and CSF rhinorrhea; 18 studies described sensitivities ranging from 65% to 94% . One hundred and eighty‐one abstracts described CTC and CSF rhinorrhea; 10 studies reported sensitivities ranging from 33% to 100% .…”
Section: Methodsmentioning
confidence: 99%
“…8,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] One hundred and twenty-four abstracts described MRC and CSF rhinorrhea; 18 studies described sensitivities ranging from 65% to 94%. 8,16,[18][19][20][21][22][23][25][26][27][28][29][30][31][32][33][34] One hundred and eighty-one abstracts described CTC and CSF rhinorrhea; 10 studies reported sensitivities ranging from 33% to 100%. 8,13,18,19,21,22,27,29,35,36 Specific details regarding screened studies and estimated sensitivities are presented in the Appendix.…”
Section: Methodsmentioning
confidence: 99%